2004
DOI: 10.1093/hmg/ddh260
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 mRNA expression levels as an indicator of chemoresistance in lung cancer

Abstract: Lung cancer is the most common cancer, with dismal outcome. Treatment approaches, including cisplatin-based chemotherapy and surgery, are currently based on the clinical classification of the tumor, without genetic assessment for predicting differential chemosensitivity. BRCA1 plays a central role in DNA repair, and decreased BRCA1 mRNA expression in the human breast cancer HCC1937 cell line caused cisplatin hypersensitivity, but the relation between BRCA1 and survival in lung cancer patients has never been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
202
3
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(223 citation statements)
references
References 26 publications
12
202
3
6
Order By: Relevance
“…In a variety of malignancies including OC, enhanced expression of the DNA repair proteins, Breast Cancer 1 (BRCA1) and excision repair cross complementation group 1 (ERCC1), have correlated with resistance to platinum. [2][3][4][5][6] In vitro models have shown that targeting the expression of both BRCA1 and ERCC1 sensitizes cells to platinum-based chemotherapeutic agents, suggesting a potential clinical application to help overcome platinum resistance in OC.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In a variety of malignancies including OC, enhanced expression of the DNA repair proteins, Breast Cancer 1 (BRCA1) and excision repair cross complementation group 1 (ERCC1), have correlated with resistance to platinum. [2][3][4][5][6] In vitro models have shown that targeting the expression of both BRCA1 and ERCC1 sensitizes cells to platinum-based chemotherapeutic agents, suggesting a potential clinical application to help overcome platinum resistance in OC.…”
mentioning
confidence: 99%
“…Although BRCA1 deficiency is generally associated with improved prognosis after platinum-based treatment, not all reports have validated this finding, 12,13 indicating that further studies are needed. Interestingly, low BRCA1 expression has been shown to have prognostic significance in sporadic breast cancer 14 and has correlated with prognosis after platinum-containing chemotherapy in non-small cell lung cancer (NSCLC), 3 suggesting BRCA1 may have a significant role as a biomarker in various tumor types.…”
mentioning
confidence: 99%
“…I N addition to substitutions at the protein level, changes in gene regulation are likely to underlie many phenotypes of interest, including adaptations and human diseases (Britten and Davidson 1971;King and Wilson 1975;Jin et al 2001;Carroll 2003;Abzhanov et al 2004;Iftikhar et al 2004;Shapiro et al 2004;Taron et al 2004). Regulation of gene expression may be achieved by a large number of transcriptional and translational mechanisms (reviewed in Wray et al 2003).…”
mentioning
confidence: 99%
“…However, the relatively narrow range of ERCC1 expression in the mid-range of the maximal expression spectrum suggests that MBC is only moderately platinum sensitive, and that ERCC1 expression levels may not be useful for therapeutic decisions on platinum use for MBC [23]. In contrast, BRCA1 expression levels had a wide range in MBC, which may provide an opportunity for its use as a predictive marker for platinum efficacy [24]. However, in contrast to RRM1 and ERCC1 where activating or inactivating mutations have not been described, assessment of the mutational status of BRCA1 may be crucial to the interpretation of the prognostic and predictive utility of its protein levels [25][26][27].…”
Section: Discussionmentioning
confidence: 99%